Bidirectional Association between Psoriasis and Asthma: A Systematic Review and Meta-Analysis - Ashley Garcia; Prakash V. A. K. Ramdass; Maria E. Ramos-Nino (MDPI AG, 2023)
Background: Studies have shown an increased risk of asthma in patients with psoriasis and vice versa. Thus, we conducted a meta-analysis to estimate the pooled association between these two chronic inflammatory diseases. Methods: A systematic search of the literature was conducted through March 2023. Risk ratios (RRs) and prevalence were calculated. Results: A total of 11 studies comprising 110,978 patients with psoriasis and 1,898,071 controls were included in the first meta-analysis. The prevalence of asthma in patients with psoriasis was 9.2% (0.075, 0.110), and the pooled risk ratio (RR) was 1.43 (1.23,1.66). Subgroup analysis showed that older patients (≥50 years) have a higher pooled risk of asthma [RR 1.59 (1.41, 1.79)] than younger patients (20-49 years) [RR 1.23 (1.07,1.41)]. In addition, a significantly higher risk of asthma was seen in patients with moderate to severe psoriasis [RR 1.48 (1.17, 1.88)) when compared to their controls than those with mild psoriasis [RR 1.28 (1.14, 1.44)]. A total of 3 studies comprising 468,869 asthma patients and 11,063,349 control were included in the second meta-analysis. The prevalence of psoriasis in asthma patients was 1.3%, 0.004, 0.029), and the pooled risk ratio was 1.23 (1.02,1.47). Conclusions: This meta-analysis provides clear evidence for the bidirectional association between asthma and psoriasis.